Parametric Interaction-Induced Asymmetric Behaviors in a Coupled-Cavities Quantum Electrodynamics System - Xu Ma; Dexi Guo; Chengjie Zhu; Jingping Xu (Photonics, 2025)
We investigate a quantum electrodynamics system consisting of two coupled single-mode cavities. The left cavity couples with a two-level atom, while the right cavity incorporates a second-order nonlinear medium, activated by a pumping field. In the absence of nonlinear medium, we show that the transmitted field intensity reveals only classical asymmetric behavior at the central frequency. However, the parametric interaction induced by the nonlinear medium leads to various quantum asymmetric behaviors at single photon excitation frequencies, including the squeezing, quantum statistics, and phase-space characteristics of the transmitted photons. These asymmetric behaviors arise from additional excitation pathways enabled by the parametric interaction-induced two-photon processes. We demonstrate these asymmetric behaviors through Klyshko’s figures of merit, the Wigner function, and the steady-state second-order correlation function of the transmitted photons. These results present promising applications for remote quantum-state manipulation and contribute significantly to the advancement of quantum networking.